DNA cleavage activity of VIVO(acac)2 and derivatives - Butenko, Nataliya (2013)
The DNA cleavage activity of several b-diketonate vanadyl complexes is examined. Vanadyl acetylacetonate,VIVO(acac)2, 1, shows a remarkable activity in degrading plasmid DNA in the absence of any activating agents, air and photoirradiation. The cleaving activity of several related complexes VIVO(hd)2(2, Hhd = 3,5-heptanedione), VIVO(acac-NH2)2 (3, Hacac-NH2 = acetoacetamide) and VIVO(acac-NMe2)2(4, Hacac-NMe2 = N,N-dimethylacetoacetamide) is also evaluated. It is shown that 2 exhibits an activity similar to 1, while 3 and 4 are much less efficient cleaving agents. The different activity of the complexes is related to their stability towards hydrolysis in aqueous solution, which follows the order 1 2 3 4.The nature of the pH buffer was also found to be determinant in the nuclease activity of 1 and 2. In a phosphate buffered medium DNA cleavage by these agents is much more efficient than in tris, hepes,mes or mops buffers. The reaction seems to take place through a mixed mechanism, involving the formation of reactive oxygen species (ROS), namely OH radicals, and possibly also direct cleavage at phosphodiester linkages induced by the vanadium complexes.